Pengaruh Kompetensi Terhadap Kinerja Guru Di Madrasah Aliyah Negeri Luwu Kecamatan Suli, Kabupaten Luwu - Ardiansyah Ali; Andi Musfirawati Nur; Nurlela Nurlela (Economy Deposit Journal (E-DJ), 2021)
This school is located in Lempopacci, Suli, Luwu Regency, South Sulawesi, on Jalan Pendidikan No. 10.The Luwu State Madrasah, Suli District's vision is to improve intelligence, knowledge, personality, noble character, and skills.The goal of this study was to see how competence affected teacher performance in Madrasah Aliyah Negeri Luwu, Suli District, in terms of producing students with noble character to become Madrasah Aliyah teachers. With a population of 45 people, the sampling method used in this study is Arikunto's theory, with 35 permanent and non-permanent teachers at Madrasah Aliyah Negeri Luwu, Suli District. Then, based on the coefficient of determination, it shows that the independent variable (competence) is moderately correlated with changes in the performance of Madrasah Aliyah Negeri Luwu teachers